Ancillary methods to improve diagnostic accuracy of thyroid nodules on fine-needle aspiration cytology smears - Van Wyk, Christine (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScMed (Dept. of Biomedical Sciences. Anatomy and Histology) --University of Stellenbosch, 2007.